TUNED IPC WITH TWO DEGREES OF FREEDOM - Kalinin L.P.; Zaitsev D.A.; Tirshu M.S. (Problems of the Regional Energetics, 2006)
This paper introduces a new family of IPC-UPFC combination for independent control of active and reactive output power, the control strategy is presented to maintain the required power characteristics.